Yishen capsule promotes podocyte autophagy through regulating SIRT1/NF-κB signaling pathway to improve diabetic nephropathy. Issue 1 (1st January 2021) - Liu, Yuxiang; Liu, Wenyuan; Zhang, Ziyuan; Hu, Yaling; Zhang, Xiaodong; Sun, Yanyan; Lei, Qingqing; Sun, Dalin; Liu, Ting; Fan, Yanjun; Li, Hui; Ding, Wujie; et al.
Abstract: Diabetic nephropathy (DN) is a common complication of diabetes. Yishen capsule, composed of Chinese herbs, improves the clinical outcome in DN patients. However, its therapeutic potential and underlying mechanisms require further elucidation. Hence, our study aimed to investigate the underlying mechanisms and therapeutic potential of Yishen capsule in DN. Streptozotocin-induced DN rats were treated with Yishen capsules (1.25 g/kg/day) for 8 weeks. Then, blood glucose and urine protein levels were measured. Hematoxylin and eosin staining and western blot assays were used to examine the histologic changes and gene expression, respectively, in kidney samples. Mouse podocytes were treated with rat serum containing Yishen capsule and transmission electron microscopy was used to examine autophagosome formation. Cell counting kit-8 assay was performed to examine cell proliferation. Western blot and reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analyses were conducted to detect changes in gene expression. The localization of SIRT1 was examined in the podocytes using immunocytofluorescence assay. We found that Yishen capsule relieved pathological changes, decreased urine protein, increased SIRT1, LC3-II, and Beclin-1 expression, and reduced acetylated NF-κB p65 expression in vivo . In addition, rat serum containing Yishen capsule showed improved podocyte proliferation, promoted the mRNA and protein levels of LC3-II and Beclin-1, and induced nuclear translocation of SIRT1. Furthermore, it increased SIRT1 expression and decreased mRNA level of NF-κB in the serum. SIRT1 inhibitor increased the mRNA level of NF-κB. Our data suggests that Yishen capsule improves DN by promoting podocyte autophagy via the SIRT1/NF-κB pathway.